An Investigation of Communication Needs Experienced by Non-native Speakers of English as a Lingua Franca Academic Context - Tanaporn Khamwan (Journal of Humanities and Social Sciences Mahasarakham University, 2023)
This study investigates common communication needs encountered in an ELF academiccontext. The participants consisted of two Thai professors, fifteen Thai, and fifteen Cambodian students who studied in grade 12 and enrolled at the university where ELF was used in an academic context. A semi-structured interview was used to collect daaitwhich was analyzed by coding method. The findings revealed two primary common communication needs shared between Thai students and Cambodian student: There are -1) limited linguistic knowledge, which contained three aspect;: comprehension skill, grammatical errors, and inadequate vocabulary, and 2) sociocultural bias, which contained two aspect;: cultural bias and mindset, which led to unsuccessful communication.